An Analytical Method to Predict the Structural Behavior of Timber-Concrete Structures With Brittle-to-Ductile Shear Connector Laws. (15th October 2020) - Nguyen, Truong-Thanh; Sorelli, Luca; Brühwiler, Eugen
Highlights: A new analytical solution for predicting non-linear structural response of TCC beams with ductile connectors. Validated the proposed method against Finite Element methods and other existing methods. Developed a design table for estimating the structural behaviour point-by-point from the ductile connector law. Considered the effect of slab concrete cracking. Considered the effect of different strength class of concrete, i.e., from normal concrete to UHPFRC. Abstract: Timber-Concrete Composite (TCC) structures allow taking synergistic advantage of the properties of both materials to optimize the overall performances in terms of lightness, slenderness, acoustic insulation, vibrational behaviour and environmental footprint. In the last years, ductile shear connectors have been developed to allow the structural ductility of TCC structures. Considering the limitations of current design methods, this work aims at developing a closed-form solution for accurately predicting the nonlinear structural response of a TCC structure directly from the materials' property and the shear law of ductile connectors. In particular, we have assumed a generalized shear law based on 3 parameters which allow considering shear law from a pure elasto-plastic to pure brittle behaviour. After a short introduction, Section 2 briefly presents the basics of the well-estabilished elastic theory for a 2-layer composite beam with a linear shear law in terms of horizontal shear vs. slip (Vh -s) law; Section 2.3 extends the semi-analytical method proposed by Bažant and Vitek for composite structures with a generalized shear law; Sections 3 extends the previous method by developing a new closed-form analytical solution for predicting the TCC structural response for a generalized elasto-plastic Vh -s shear law described by an initial linear response up to Vmax followed by a plastic plateau at a constant load, which can range from 0 to Vmax ; Section 4 compares the model results with the ones of existing methods and FEM analysis. Furthermore, a parametric analysis is carried out to investigate the model sensitivity to the connector parameters; Finally, Section 5 presents a simple point-by-point design procedure of which prediction accuracy of the ultimate moment, deflection and slip was statistically assessed for a large range of possible TCC structures against FEM analysis. Eventually, the effect of concrete cracking is also considered and a correction factor is proposed for engineering purpose.